The Amish widow's heart - Perry, Marta (Perry, Marta. Brides of Lost Creek., 2020)
To secure her young son<U+2019>s future, widow Bethany Esch steps in to help Daniel Miller keep the store he owned with her late husband running smoothly. But she soon discovers her marriage hid a stunning secret. Though Daniel had no knowledge of her husband<U+2019>s clandestine life, he<U+2019>ll now do anything to help Beth. But can his steadfastness convince her to forgive<U+2014>and love once more?